The holy land reborn : pilgrimage & the Tibetan reinvention of Buddhist India - Huber, Toni, 1956- (Chicago : University of Chicago Press, 2008)
The Dalai Lama has said that Tibetans consider themselves 'the child of Indian civilization' and that India is the holy land from whose sources the Tibetans have built their own civilization. This work looks at this relationship and how Tibetans have maintained it, particularly by way of pilgrimage.
List of Figures; Acknowledgments; Note on Transliteration; Introduction; Part One: Locating and Dislocating the Land of the Buddha; 1 The Shifting Terrain of the Buddha; 2 Buddhist Knowledge and Anachronism in Tibet; 3 Journeying to the Centre of the World; 4 Tantric Buddhist India and Its Tibetan Appropriation; Part Two: Reinventing the Holy Land in India; 5 Nirvana in Assam; 6 Return to the Centre of the World; 7 The Allure of the Atsaras; 8 The Precious Guru in the Punjab; Part Three: Modern Rebirths of the Holy Land; 9 Archaeological and Discursive Rebirths of Buddhist India.
Includes bibliographical references (pages 439-483) and index.
Print version record.
Master record variable field(s) change: 650, 651
Keywords: Buddhist pilgrims and pilgrimages -- India; Buddhist pilgrims and pilgrimages -- China -- Tibet Autonomous Region; Sacred space -- India; Tibet Autonomous Region (China) -- Relations -- India; India -- Relations -- China -- Tibet Autonomous Region; RELIGION -- Buddhism -- Rituals & Practice; Buddhist pilgrims and pilgrimages; International relations; Sacred space; China -- Tibet Autonomous Region; India; Electronic books